HPLC Determination of Chlorophenols in Water with Separation by Ionic Liquids [Bmim]BF4 Aqueous Two-phase Solvent Sublation - Wang, Liang; Zhu, Hong; Ma, Chunhong; Yan, Yongsheng (Asian Journal of Chemistry, 2012)
2,4-Dichlorophenol, 2,6-dichlorophenol and 4-chlorophenol were separated from water sample and enriched by ionic liquids [Bmim]BF4 aqueous two-phase solvent sublation with [Bmim]BF4 as solvent from the water sample at pH 10.70 and flotation with nitrogen at a flow rate of 35 mL min-1, for 40 min. At the end of sublation, 10 μL of the supernatant ionic liquids phase were taken for HPLC analysis. Detection limits (3s/b) of three chlorophenols were 15, 22 and 10 μg L-1, respectively. Tests for recovery were made with a blank water sample as matrix by standard addition method, values of recovery were found in the range of 90-102 %, with values of RSD's (n = 11) ranged from 1.5 % to 4.3 %.